Cover Feature: Spontaneous Preparation of Monodispersed, Structural Colored, Spherical Particles by Rotational Stirring (ChemNanoMat 7/2018). Issue 7 (20th June 2018) - Teshima, Midori; Suzuki, Motoki; Seki, Takahiro; Takeoka, Yukikazu
Abstract : When rotational stirring was applied to an electrically neutral aqueous suspension containing negatively charged, monodispersed silica fine particles and a positively charged polyelectrolyte, monodispersed, spherical particles with a size of several hundred micrometers were obtained. Additionally, monodispersed, spherical particles with a vivid structural color can be prepared by incorporating a small amount of a black substance in the spherical particles. More information can be found in the Communication by Yukikazu Takeoka et al. onpage 621 in Issue 7, 2018 (DOI:10.1002/cnma.201800102 ).